Contributions of sport psychology to competitive gymnastics - Nunomura, M.; Santos Oliveira, M. (High performance gymnastics, 2014)
The diverse behaviors observable in gymnastics result from the interplay of person acting in a particular environment with regard to specific tasks. A person-task-environment fit is a significant precondition for a gymnasts' optimization of actions in a particular situation (e.g., competition) and thus for the attainment of peak performance. There are several personality traits and psychological states that seem to be related to gymnasts' performance, development, and mental health. Continually practicing psychological skills and strategies may influence psychological states in the short run. These changes in psychological states may in turn lead to changes in personality traits in the long run, leading to enhancements in personality development, which should be considered positive in nature (Salmela, Petiot, & Hoshizaki, 1987). In order to support gymnasts' development, effective coaching strategies should be applied. Effective coaching is characterized by an open communication and the presence of coaches' rewarding behavior for gymnasts' effort and performance. The coach and the gymnasts feel respect for one another and appreciate each other's roles. Elite gymnasts not only possess specific psychological states but also regulate complex skills more precise than their less-skilled counterparts. Dramatic changes in psychological states are thought to be a potential precondition for movement errors, injuries or even for a loss of skill. Experienced gymnasts are far from being 'machines' that produce the same pattern of movement in every trial. Even if this might look so at first sight, biomechanical analyses usually reveal that there will always remain some trial-to-trial variability, and the question would be which (psychological) factors influence this variability and when does this variability support and when does it hamper performance. It can finally be stated, that gymnastics coaches are advised to apply state-of-the art knowledge on psychological methods in a personcentered approach when working with gymnasts on all ages. Psychological methods can be thought of as a set of tools that gymnast could use to optimize his/her psychological states and in turn to optimize subjective and objective performance. To be effective, the methods should be practiced in a systematic and regular manner, and they should be integrated into physical training in such a way, that the gymnast is able to personalize and claim ownership of the methods for his/her individual needs.